2008
DOI: 10.1002/prca.200780075
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myofilaments: from proteome to pathophysiology

Abstract: This review addresses the functional consequences of altered post-translational modifications of cardiac myofilament proteins in cardiac diseases such as heart failure and ischemia. The modifications of thick and thin filament proteins as well as titin are addressed. Understanding the functional consequences of altered protein modifications is an essential step in the development of targeted therapies for common cardiac diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 110 publications
0
22
0
Order By: Relevance
“…Myofilament protein PTMs have emerged as a key mechanism regulating cardiac contractility, and increasing evidence has shown that the alteration of myofilament protein PTMs, particularly phosphorylation, can contribute to contractile dysfunction and heart failure [912, 25, 26, 29, 30]. Additionally, studies in humans, as well as large and small animals, have shown that aging and pathological cardiac conditions induce transmural changes in contractile function that correlate with differences in the modification status of myofilament proteins [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myofilament protein PTMs have emerged as a key mechanism regulating cardiac contractility, and increasing evidence has shown that the alteration of myofilament protein PTMs, particularly phosphorylation, can contribute to contractile dysfunction and heart failure [912, 25, 26, 29, 30]. Additionally, studies in humans, as well as large and small animals, have shown that aging and pathological cardiac conditions induce transmural changes in contractile function that correlate with differences in the modification status of myofilament proteins [1, 2, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Contractile heterogeneity, in particular, has taken on increased significance with the demonstration that transmural changes in myocardial contractility not only occur in the failing heart [13], but may also be predictive of adverse cardiac events [7, 8]. Myocardial contractility is governed by a number of factors, including the size and duration of Ca 2+ transients, as well as the intrinsic properties of the contractile apparatus, which depend primarily on the expression of myofilament protein isoforms and post-translational modifications (PTMs) [912]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofilaments are the essential components of the contractile apparatus and the sliding of them generates contraction . Myofilaments consist of thin and thick filaments (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our first goal was to assess sarcomeric contractile properties by measuring direct isometric forces on skinned isolated cell preparations. Second, since the cardiac sarcomeric proteins myosin binding protein C (MyBPC), troponin T (TnT), troponin I (TnI), tropomyosin (Tm), and regulatory myosin light chain (MLC-2) are known to effect contractility, 13 we assessed whether post-translational modifications and/or other alterations in these proteins were affected with LVAD support.…”
mentioning
confidence: 99%